PENGGUNAAN METODE LANGSUNG DALAM PEMBELAJARAN MUHADATSAH - Miswarul Abdi Azizi (Jurnal Pendidikan dan Pengajaran, 2023)
Method is the way that must be taken to achieve a goal. So that the two important things contained in a method are how to do something and the plan for implementation. The better the method used, the more effective the achievement of goals. To determine in advance whether a method can be called good, a benchmark is needed that comes from several factors. The main determining factor is the goal to be achieved. By having a general understanding of the nature of the various methods, a teacher will more easily determine which method is most suitable for the situation and teaching conditions he wants to apply. The direct method uses more activities in learning. This method places more emphasis on listening and speaking, then emphasizes the accuracy of pronunciation and grammar, communication skills are developed by discussing questions and answers in class, and what is more interesting is that the learning uses demonstrations such as visual aids. There are also many interesting ways to teach this method, such as games based on this method.